Acoustic white noise ameliorates reduced regional brain expression of CaMKII and ΔFosB in the spontaneously hypertensive rat model of ADHD. (June 2019) - Eckernäs, Daniel; Hieronymus, Fredrik; Carlsson, Thomas; Bergquist, Filip
Highlights: ΔFosB was reduced in the DL-PFC, DLS and nAc in SH rats. Acoustic noise normalized ΔFosB expression in the DL-PFC and nAc of SH rats. CaMKII expression was reduced in the TMN in SH rats. Acoustic noise increased CaMKII expression in the TMN in both strains. Abstract: Loud (≥70dBA) acoustic white noise improves cognitive performance in children with ADHD as well as skilled reach and rotarod performance in the spontaneously hypertensive (SH) rat model of ADHD. To investigate how acoustic noise influences the brain activity in the SH rat model of ADHD, immunohistochemical staining of two neuronal activity and plasticity markers, Ca 2+ /Calmodulin dependent protein kinase II (CaMKII) and ΔFosB, was evaluated in Wistar (n = 24) and SH (n = 16) rats after repeated exposure to acoustic noise or ambient silence. Other SH rats (n = 6) were treated with repeated methylphenidate (MPH). Expression of CaMKII was reduced in the tuberomammillary nucleus (TMN) of the SH rat compared to Wistar but not in the nucleus accumbens (nAc) or the dorsolateral prefrontal cortex (DL-PFC). In the TMN, the expression of CaMKII was increased by noise in both strains. ΔFosB expression was reduced in nAc, DL-PFC and the dorsolateral striatum (DLS) of the SH rat compared to Wistar. Exposure to acoustic white noise significantly increased ΔFosB expression in the nAc and DL-PFC but not in the DLS of SH rats. The results indicate that acoustic noise shifts a reduced neuronal activity in the nAc, TMN and DL-PFC in SH rats toward the normal levels of activity in outbred rats. This may explain why noise has benefit selectively in ADHD.